Aktivitas Antimikroba Ekstrak Etanol Rimpang Kunyit, Jahe, dan Lengkuas dalam Kombinasi menggunakan Metode Checkerboard - Muhammad Azhari; Riki Febriansyah Sengaji (Journal Borneo, 2023)
Bacterial infection remains a significant problem around the globe and worsens with the emergence of antibiotic-resistant strains. Indonesia is rich in natural resources, such as its flora diversity, with various benefits, including medicinal use. This study investigated the potency of turmeric, ginger, and galangal rhizome ethanol extracts in single and combination using the checkerboard method against several pathogens. The most potent inhibitory activity in a single form was shown by turmeric extract against Streptococcus mutans and Cutibacterium acne with the minimum inhibitory concentration (MIC) value of 16 µg/mL. Meanwhile, the bactericidal activity was shown best by turmeric extract against Staphylococcus aureus and Enterococcus faecalis with both MIC and minimum bactericidal concentration (MBC) of 32 µg/mL. The synergistic combination was shown by turmeric-ginger (TGi), turmeric-galangal (TGa), and ginger-galangal (GiGa) against Staphylococcus aureus with the FICI (fractional inhibitory concentration index) of 0.15625, 0.1328, and 0.15625, respectively, and TGi against Streptococcus mutans with the fractional inhibitory concentration index (FICI) of 0.1875. This preliminary study showed the potency of those rhizomes for further research to investigate the active compounds with a synergistic activity that may be used as an alternative therapy in the future.